2014
DOI: 10.1007/s00412-014-0484-7
|View full text |Cite
|
Sign up to set email alerts
|

Do lamin A and lamin C have unique roles?

Abstract: The A-type lamins, lamin A and lamin C, generated from a single gene, LMNA, are major structural components of the nuclear lamina. The two alternative splice products have mostly been studied together because they have been considered to be interchangeable. However, several lines of evidence indicate that in spite of being generated from the same gene and having high similarities in their primary sequences, the two isoforms are not equivalent in different biological aspects in both health and disease. The key … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 97 publications
1
32
0
Order By: Relevance
“…Two LMNA spliced forms (lamin C and lamin A ∆50) even seem to have opposite functions in the context of energy metabolism (Lopez-Mejia et al 2014). It is known that lamins A and C have different expression patterns and binding properties, and it was proposed that the imbalance between those spliced forms can result in pathogenesis (Al-Saaidi and Bross 2015). As observed in our study, lamin C redistribution may suggest the mechanism of this disturbance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two LMNA spliced forms (lamin C and lamin A ∆50) even seem to have opposite functions in the context of energy metabolism (Lopez-Mejia et al 2014). It is known that lamins A and C have different expression patterns and binding properties, and it was proposed that the imbalance between those spliced forms can result in pathogenesis (Al-Saaidi and Bross 2015). As observed in our study, lamin C redistribution may suggest the mechanism of this disturbance.…”
Section: Discussionmentioning
confidence: 99%
“…Although they share many functions, they have different expression patterns, regulatory mechanisms, or assembly properties in different tissues (Al-Saaidi and Bross 2015). The targeting of lamin C and some other proteins (e.g., emerin) to the NE depends on lamin A localization (Pugh et al 1997; Vaughan et al 2001), but it is not clear how lamin mutations influence this process.…”
Section: Introductionmentioning
confidence: 99%
“…B-type lamins, which include lamins B1, B2 and B3, are encoded by the LMNB1 and LMNB2 genes (Gruenbaum et al 2005). Lamins A and C have generally been believed to display functional redundancy, although several lines of evidence indicate that these proteins may have unique biological roles in cell division, embryonic development, and aging (Al-Saaidi & Bross 2015). Lamins have multiple functions and play critical roles in DNA replication and transcription, cell division, and in providing integrity to the chromatin and nuclear membrane of various cell types (Hutchison 2002;Dechat et al 2008).…”
Section: Genetic Basis Of Hgpsmentioning
confidence: 99%
“…Lamin A and lamin C proteins constitute the main structural proteins of the inner nuclear envelope. Both isoforms are encoded by the LMNA gene, and are formed after alternative splicing . They are expressed in almost all differentiated tissues, including the myocardium and fibroblasts.…”
Section: Introductionmentioning
confidence: 99%
“…They are expressed in almost all differentiated tissues, including the myocardium and fibroblasts. In addition to their structural and supportive function of the nucleus, these proteins are believed to influence regulation of gene expression through an interaction with transcription factors, DNA, and chromatin . It has been suggested that haploinsufficiency is the disease mechanism in patients carrying truncating LMNA mutations, while LMNA missense mutations have been proposed to act through a dominant negative pathway .…”
Section: Introductionmentioning
confidence: 99%